Large erupted complex odontoma in posterior mandible: a rare case report - Munasyifa, Tazkia; Restiti, Rr Dinar; Epsilawati, Lusi; Medika, Chrisna Ardhya; Rahman, Fadhlil Ulum Abdul; Reza, Ahmad (Universitas Padjadjaran, 2025)
Introduction: Complex odontomas are hamartomas composed of randomly arranged dental tissues like enamel, dentin, cementum, and pulp. They typically have limited growth, with only 4.3% that exceed 3 cm in size. Erupted odontomas, which occur when an intraosseous odontoma erupts into the oral cavity, are exceptionally rare. This case report presents a rare case of a large complex odontoma in the posterior mandible of a woman. Case report: A 25-year-old female patient was referred to the Radiology Department with a chief complaint of left jaw swelling persisting for 6 months. Facial asymmetry was noted due to a swelling in the left jaw. Intraoral examination revealed a yellow-brown, irregular, hard mass resembling calculus. Radiographs showed a well-defined, irregular radiopaque mass approximately 6 x 3 cm in size, surrounded by a radiolucent rim. The opacity degree resembled the density of enamel and dentin in some lesion sites. Mandibular left molars were missing. Radiographic findings confirmed a diagnosis of odontoma. The patient was then referred to the Department of Oral Surgery for further management and surgical intervention. Conclusion: Odontomas rarely erupt, but their eruption and large size can lead to significant complications like pain, inflammation, infection, and facial asymmetry. Dentists should be familiar with the characteristics of odontoma to enable prompt and effective management.